Genital Hypoplasia in Gender-affirming Vaginoplasty: Prior Orchiectomy, Penile Length, and Other Factors to Guide Surgical Planning. Issue 6 (23rd December 2022) - Sineath, R. Craig; Butler, Christi; Dy, Geolani W.; Dugi, Daniel
Abstract : Purpose: Penile inversion vaginoplasty uses genital skin to construct the neovaginal canal. When genital skin is insufficient, extragenital tissue is needed. The purpose of this study is to evaluate which demographic factors and intraoperative anatomical measurements are associated with skin availability and the need for extragenital tissue. Materials and Methods: This was a prospective cohort study of patients undergoing penile inversion vaginoplasty from May 2016 through January 2021. Preoperative variables included patient demographics, orchiectomy and circumcision status, and stretched penile and scrotal skin lengths. Outcomes included measurements of available scrotal skin surface area and need for extragenital skin graft. Results: A total of 235 patients were included. Patients with prior orchiectomy and shorter stretched scrotal and penile lengths had less scrotal skin available ( P < .002) and were more likely to require extragenital skin grafts ( P < .001). Patients with prior orchiectomy had 3 times greater odds of needing additional skin grafts. Length of time exposed to gender-affirming hormones did not predict scrotal skin availability ( P = .8). Conclusions: Factors associated with need for extragenital skin grafting with penile inversion vaginoplasty were prior orchiectomy and stretched penile skin length <8 cm. Scrotal skin length >10 cm was associated with low risk for needing additional graft. Considering these factors can help with preoperative planning and patient counseling.